Clinical usefulness of hysterolaparoscopy and chromopertubation in evaluation and management of female infertility in a tertiary care hospital - N. S., Sampada; Saha, Madhuri; Uday, Rajini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Infertility is defined by the World Health Organization (WHO) as the inability to achieve pregnancy after 12 months of unprotected intercourse which affects 10–15% of couples globally. In India, prevalence ranges from 3.9% to 16.8%. Hysterolaparoscopy combined with chromopertubation (DHL + CPT) serves as a valuable diagnostic and therapeutic tool in case of female infertility. This study evaluates the effectiveness of DHL + CPT in managing primary and secondary infertility at a tertiary care hospital. Methods: In this prospective study, 60 women with primary or secondary infertility underwent clinical evaluations, basic blood tests, and abdominopelvic ultrasonography during the study period. Participants underwent DHL + CPT during their preovulatory phase following a negative urine pregnancy test. Tubal patency was assessed using methylene blue dye, and therapeutic interventions like cystectomy, adhesiolysis, ovarian drilling, septal resection were performed as necessary. Reproductive outcomes were monitored through follow-up visits or telephone correspondence. Results: Among the participants, 75% had primary infertility, and 25% had secondary infertility. Of the 32 primary infertility patients followed up, 24 (75%) conceived within six months. In the secondary infertility group, 10 out of 18 patients (55.5%) achieved pregnancy within six months. Therapeutic interventions were performed in 53% of cases, yielding promising reproductive outcomes. Conclusions: DHL + CPT is an effective, cost-efficient, and accessible method for evaluating and managing reversible causes of infertility. Patients undergoing interventions demonstrated significant improvements in fertility outcomes. However further research is warranted to explore newer, less invasive, and more cost-effective interventions.